Perkembangan Kewarganegaraan di Indonesia: Analisis dalam Perspektif Hukum Islam: The Development of Citizenship in Indonesia: An in the Perspective of Islamic Law - Ahmad Muhammad Mustain Nasoha; Ashfiya Nur Atqiya; Hukaimah; Karina Rahmawati; Dini Nurul Anisa (LITERA: Jurnal Ilmiah Mutidisiplin, 2025)
The purpose of this research is to investigate the development of citizenship in Indonesia from the perspective of Islamic law, with particular emphasis on how Islamic legal norms influence the formation of civil rights and citizenship identity in Indonesia. The study analyzed the literature and conducted a comparison between Islamic law and national law and found that the Islamic concept of citizenship emphasizes the principles of justice, equality, and human rights. The study also highlights how Indonesia's citizenship policy has changed in the last five years, as well as how Islamic law has contributed to the formation of laws related to naturalization, the rights of foreign nationals, and citizenship. The research found that Islamic law and national law are in constant flux, which enhances the conversation about citizenship rights in Indonesia, especially in the context of migration and globalization.